Get dressed! - Chwast, Seymour (New York : Abrams Appleseed, 2012)
Celebrate the daily routine of getting dressed in a book that features gatefolds which foreshadow the items of clothing to be seen and provide surprise reveals on each spread. Has die-cut magnetic closure.
Cover title.
Fold-out pages and die-cut magnetic closure.
Keywords: Clothing and dress -- Juvenile fiction; Toy and movable books -- Specimens; Clothing and dress -- Fiction